The role of progesterone and estrogen receptors in treatment choice after endometriosis surgery: A cross-sectional study - Tahereh Poordast; Saeed Alborzi; Ziba Kiani; Navid Omidifar; Elham Askary; Kefayat Chamanara; Mansoureh Shokripour; Alimohammad Keshtvarz Hesam Abadi (International Journal of Reproductive BioMedicine)
Abstract Background: The lack of improvement in some endometriotic people's pain after surgery even while using hormone treatment may suggest an inappropriate response to routine hormonal therapies. Objective: This study aimed to determine a cut-off point for selecting the most appropriate treatment based on the hormone receptors of endometriotic lesions. Materials and Methods: In this cross-sectional study, by reviewing the medical records of participants and testing their archive samples and phone interviews (if needed), 86 symptomatic women after endometriosis surgery who were operated into governmental hospitals, Shahid Faghihi and Hazrate Zeinab Shiraz Iran were enrolled between March 2017 and March 2019. Women were divided into 2 groups: responsiveness (n = 73 for dysmenorrhea, n = 60 for dyspareunia) to medical treatment and surgery, and unresponsiveness (n = 13, n = 7). We examined the pathological slides of 86 women to determine the amount of hormone receptors and the relationship between the type of medical treatment and the level of hormone receptors on pain relief within 1 yr after surgery. Results: Based on the receiver operating characteristic curve, dysmenorrhea in the presence of tissue estrogen receptors > 60% (p = 0.1065), and dyspareunia in the presence of tissue progesterone receptors > 80% (p = 0.0001) responded well to medical treatment after surgery. In the presence of endometrioma-dysmenorrhea showed the best response to oral contraceptive pills (69.4%), while in deep infiltrative endometriosis-dyspareunia showed the best response to progesterone treatment (75%). Conclusion: Prescribing an appropriate hormone therapy based on a specific immunohistochemistry staining pattern can improve the life quality of postoperative endometriosis individuals.